2018
DOI: 10.1097/md.0000000000011604
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of neuroendocrine markers, TTF-1, p53, and Ki-67 in cervical and pulmonary small cell carcinoma

Abstract: Small cell carcinoma (SCC) is a highly malignant neuroendocrine tumor that may occur in many anatomic sites of the body.In this study, we compared the different expression of neuroendocrine markers, thyroid transcription factor 1 (TTF-1), p53, and Ki-67 in 23 cases of cervical SCC and 56 cases of pulmonary SCC using immunohistochemistry.Our study showed that cervical SCC had a younger onset age than pulmonary counterpart. Although both had the similar morphological features, different immunohistochemical expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…Some studies have shown that 33%–84% of small-cell cervical carcinomas exhibit diffuse nuclear positivity for thyroid transcription factor-1 (TTF-1) 21 25–27. Liu et al 28 compared different expression of neuroendocrine markers, TTF-1, p53, and Ki-67 in 23 cases of cervical small-cell and 56 cases of pulmonary small-cell carcinomas using immunohistochemistry. The TTF-1 expression of small-cell carcinoma of the lung showed significantly higher diffuse and strong positivity in tumor cell nuclei than the cervical counterpart (p=0.003).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Some studies have shown that 33%–84% of small-cell cervical carcinomas exhibit diffuse nuclear positivity for thyroid transcription factor-1 (TTF-1) 21 25–27. Liu et al 28 compared different expression of neuroendocrine markers, TTF-1, p53, and Ki-67 in 23 cases of cervical small-cell and 56 cases of pulmonary small-cell carcinomas using immunohistochemistry. The TTF-1 expression of small-cell carcinoma of the lung showed significantly higher diffuse and strong positivity in tumor cell nuclei than the cervical counterpart (p=0.003).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The literature search identified 39 articles on IHC staining of NE markers fulfilling the criteria (see Materials and Methods). [3][4][5][6][8][9][10][11][12][13][14][15][17][18][19] In Table 4, the accumulated data from these and the current investigation are presented, also specifying data for any/at least 1% (any positivity and 1% stained tumor cells were here considered equal) and at least 10% stained tumor cells as the cutoff for a positive staining, respectively (data not provided in all studies). More details on the identified articles are found in Supplemental (Figure 4, A and B).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…1 A positive NE marker is not strictly required for SCLC, though most cases do express at least 1 such marker. 1,[3][4][5][6][7][8][9] Carcinoid tumors are typically positive for all, or at least several, NE markers. 1,[3][4][5][9][10][11] Neuroendocrine markers may also be expressed in NSCLC, [3][4][5][12][13][14][15] which may cause diagnostic problems, and staining with NE markers is only recommended if NE morphology is evident.…”
mentioning
confidence: 99%
“…Current studies have shown that E6 proteins of HPV16 and HPV18 can bind to wild-type p53 proteins, and with the participation of E6-related proteins, promote the degradation of p53 proteins, eventually lead to the reduction of p53-induced G1 phase arrest in cell cycle, thus completing DNA synthesis and promoting cell proliferation [31,32] . HPV infection also destroys normal sex hormone function, which weakens the antiestrogen effect of progesterone in endometrial lesions and increases the malignant transformation of cells [33] . HPV can induce the cell cycle activity of Ki67 positive cells.…”
Section: Table 4: the Expression Of Er Pr P53 And Ki67 In Patients mentioning
confidence: 99%